Intermittent Hypoxia Affects the Spontaneous Differentiation In Vitro of Human Neutrophils into Long-Lived Giant Phagocytes. (9th November 2015) - Dyugovskaya, Larissa; Berger, Slava; Polyakov, Andrey; Lavie, Peretz; Lavie, Lena
Abstract : Previously we identified, for the first time, a new small-size subset of neutrophil-derived giant phagocytes (Gϕ ) which spontaneously develop in vitro without additional growth factors or cytokines. Gϕ are CD66b + /CD63 + /MPO + /LC3B + and are characterized by extended lifespan, large phagolysosomes, active phagocytosis, and reactive oxygen species (ROS) production, and autophagy largely controls their formation. Hypoxia, and particularly hypoxia/reoxygenation, is a prominent feature of many pathological processes. Herein we investigated Gϕ formation by applying various hypoxic conditions. Chronic intermittent hypoxia (IH) (29 cycles/day for 5 days) completely abolished Gϕ formation, while acute IH had dose-dependent effects. Exposure to 24 h (56 IH cycles) decreased their size, yield, phagocytic ability, autophagy, mitophagy, and gp91- phox /p22- phox expression, whereas under 24 h sustained hypoxia (SH) the size and expression of LC3B and gp91- phox /p22- phox resembled Gϕ formed in normoxia. Diphenyl iodide (DPI), a NADPH oxidase inhibitor, as well as the PI3K/Akt and autophagy inhibitor LY294002 abolished Gϕ formation at all oxygen conditions. However, the potent antioxidant, N-acetylcysteine (NAC) abrogated the effects of IH by inducing large CD66b + /LC3B + Gϕ and increased both NADPH oxidase expression and phagocytosis. These findings suggest that NADPH oxidase, autophagy, and the PI3K/Akt pathway are involved in Gϕ development.